"Bribery with Chinese characteristics" and the use of guanxi to obtain admission to prestigious secondary schools in urban China. Issue 1 (2nd January 2019) - Ruan, Ji
ABSTRACT: Some scholars have attempted to find ways to distinguish guanxi from bribery, which can be difficult due to the role played by four traditional Chinese concepts and practices. First, people value the renqing ethic more than law, making it hard to judge whether a relation has "improper inducements." Second, some interaction rituals used in bribery guanxi are a type of moral performance, undertaken to justify immoral practice – this mixes together guanxi practice with bribery. Third, some of the " ganqing " (affection) and esteem expressed in bribery guanxi results from this moral performance, rather than from genuine affection and esteem. Fourth, some people try to embody their relationship as an enduring guanxi, rather than one-off bribery, which exacerbates the difficulty in distinguishing guanxi from bribery. Because of the moralizing culture and the custom of mixing together renqinq and bribery, it can be difficult to distinguish bribery from guanxi by attempting to judge whether an action is purely based on esteem or coercion, on an enduring relationship or a one-off exchange, on improper inducement or proper conduct, or other such formal distinctions.